GLOBAL RESEARCH TRENDS ON OIL PALM WASTE-BASED AS SOUND ABSORPTION MATERIAL: A BIBLIOMETRIC ANALYSIS - Salim, Nurliza; Abu, Aminudin; Bakar, Balkis Fatomer A.; Othman, Nor’azizi; Anis, Samsol Faizal (INTERNATIONAL JOURNAL OF INNOVATION AND INDUSTRIAL REVOLUTION (IJIREV), 2026)
The increasing demand for sustainable acoustic materials has accelerated research into renewable biomass resources as environmentally friendly alternatives to conventional synthetic absorbers. Among these resources, oil palm waste has received increasing attention due to its abundance, renewability and the potential suitability for sound absorption applications. However, despite the growing literature, comprehensive bibliometric evidence describing publication trends, collaboration networks, thematic evolution and emerging research directions remains limited. Therefore, this study attempts to perform a bibliometric analysis to assess global research trends on oil palm waste-based sound absorption material. Bibliometric data were extracted from the Scopus database and analysed using VOSviewer, Scopus Analyzer and Scopus AI to identify publication trends, highly cited publications, co-occurrence patterns of keywords, leading contributing countries and international collaboration networks. The results showed a significant increase in publications after 2010, indicating growing scientific interests in the utilisation of oil palm biomass for sustainable acoustic applications. Furthermore, citation analysis also demonstrated that the most cited studies were mostly related to composite materials, thermal performance and sustainable engineering applications. The keyword co-occurrence analysis identified acoustic performance, material characterisation and multifunctional engineering material, whereby the leading research themes placed Malaysia as the main contributor and the collaborator hub. Notably, the strong interconnection between mechanical properties, sound absorption, thermal conductivity, density, natural fibres and oil palm biomass suggests that research trends increasingly emphasise integrated performance optimisations rather than isolated acoustic assessment. Thus, this field has evolved from agricultural waste utilisation towards multifunctional material development involving acoustic, physical, thermal and mechanical optimisation. The findings contribute to SDG 9 (Industry, Innovation and Infrastructure), SDG 11 (Sustainable Cities and Communities), SDG 12 (Responsible Consumption and Production) and SDG 13 (Climate Action) by supporting sustainable material innovation and biomass valorisation strategies.